Expiry as a Form of Extinction of Demanial Concessions and the Guarantees of the Concessionaire: The Case of the Mining Concessions - Ghazzaoui Piña, Ramsis (2015)
In the present article, the autor seeks to explain us the juridical nature of mining concession, thus by explaining the concessional technique and the juridical effects that come along with it. For this purpose, a doctrinaire and legal analysis of mining concession and the legal institution is done.